Руйнування і охорона археологічних пам'яток у Криму (кінець 40-х – 60-ті рр. ХХ ст.) - Соколов, А.А. (Праці Центру пам’яткознавства, 2013)
Репрезентовано заходи з охорони та використання археологічних пам'яток Криму наприкінці 40-х – у 60-х рр. XX століття. На основі широкого кола неопублікованих джерел розкрито діяльність державних органів влади у цьому напрямку. Через призму культурної політики Радянського уряду продемонстровано ставлення до пам'яток з боку місцевої влади. Наведено аналіз прийнятих практичних заходів та їх ефективності. Особливу увагу приділено знищенню та пошкодженню пам'яток. Приведено найбільш показові в цьому плані приклади. Виокремлено основні причини, що приводили до їх руйнування. Окреме значення відводиться впливу господарської діяльності та освоєння земель під будівництво на стан археологічних пам'яток. Висвітлено участь музеїв в охороні пам'яток. Праналізовано масштабні роботи з консервації та реставрації руїн Херсонесу. Освещены вопросы охраны и использования археологических памятников
Крыма в конце 40-х – 60-х годов XX века. На основе широкого круга неопубликованных источников раскрывается деятельность государственных органов в этом направлении. Через призму культурной советской политики продемонстрировано
отношение к памятникам со стороны местных властей. Приводится анализ принятых практических мероприятий и их эффективности. Большое внимание уделяется уничтожению и повреждению памятников. Приведены, наиболее показательные в
этом плане примеры. Выделяются основные причины, которые приводили к их
разрушению. Особое значение придается влиянию хозяйственной деятельности и
освоению земель под строительство, состоянию археологических памятников. Освещается участие музеев в охране памятников. Анализируются масштабные работы по консервации и реставрации руин Херсонеса. The article is dedicated to the protection and use of archaeological sites of the Crimea
in the late 40's – 60's of the XX century. On the basis of a wide range of unpublished
sources revealed the activity of state bodies in this direction. Through the prism of Soviet
cultural policy demonstrated by the ratio of the monuments to the local authorities. The
analysis of the practical measures taken and their effectiveness. Particular attention is paid
to the destruction and damage to monuments. Shows, the most significant in this respect
examples. Highlights the main reasons led to their destruction. Particular importance is
attached to the influence of economic activities and development of land for construction,
the condition of the monuments. Archaeological sites of the Crimea during the period
under review was one of the most vulnerable categories of cultural heritage. Plans for
socio-economic development of the region were going to cut the need for their protection.
In the early postwar years, the problem in the shortest time to restore the ruined city gave
rise to virtually uncontrolled destruction of monuments to the quarry. The government has
attempted to make the case monuments more regimented nature. To do this, issued a series
of regulations to the regulatory and legal framework in this sphere. However, in spite
of all the positive aspects of such decisions, in fact, they were far from absolute performance.
Primarily due to the fault of the local authorities are often indifferent to the fate of
monuments. District and city executive committees sometimes deliberately did not respond
to numerous violations of the existing legislation. During the reign of Khrushchev
in the state and party leadership once again prevailed ideology of nihilism and utilitarian
views. Stop funding any repair and restoration work. As a result, many sites have come to
an even greater dilapidation. Since the early 60's., XX century, because of the wide scope
of construction work and agricultural land development, more and more of them in the
area began to fall archaeological sites. Plans for the Soviet, demanded the speedy construction
of civil and industrial projects. The pace of archaeological research has not keep
up the pace of construction. Most construction took place at all without any coordination
with the archaeologists in the lands are of great scientific interest. Some measures taken
by the local authorities as a whole could drastically improve on the existing system of
protection of monuments. Further development monuments case required the creation of a
single, unified legislative act, with a clear indication of the norms and rules of protection,
as well as liability for their violation.